1996
DOI: 10.1007/bf02873855
|View full text |Cite
|
Sign up to set email alerts
|

Lead uptake, localization and changes in cell ultrastructure ofFunaria hygrometrica protonemata

Abstract: The main sites of lead entering the protonemata were spores with broken cell walls and apical cells of protonemata. The lead ions could enter the symplast probably by endocytosis but we can not exclude diffusion as the way of entering. Lead deposits inside a protoplast were observed after 2 h of lead application. After 12 h, Pb deposits were commonly present in all cell structures surrounded by a membrane. Some disturbances in ultrastructure of organelles were found after 8 h. The most frequent were: change of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…However, Maisnier-Patin andRichard (1996) reported that exposure of Listeria innocua to nisin concentrations of 500 and 4000 IU ml )1 induced cell wall thickening as well as irregularities. Krzesłowska and Woźny (1996) founded that 48 h-treatment 4 lmol l )1 PbCl 2 resulted in cell wall thickening at the tip of the apical cell.…”
Section: Discussionmentioning
confidence: 96%
“…However, Maisnier-Patin andRichard (1996) reported that exposure of Listeria innocua to nisin concentrations of 500 and 4000 IU ml )1 induced cell wall thickening as well as irregularities. Krzesłowska and Woźny (1996) founded that 48 h-treatment 4 lmol l )1 PbCl 2 resulted in cell wall thickening at the tip of the apical cell.…”
Section: Discussionmentioning
confidence: 96%
“…CW thickenings appeared at the tip of apical cells (Fig. 2d, f), one of the main sites of Pb uptake (Krzesłowska and Woźny 1996). It was striking that the nature of the F. hygrometrica thickenings markedly differed from that of the CW in unexposed plants.…”
Section: Cell Wall Thickeningsmentioning
confidence: 95%
“…Hence, TMs, already present within the endomembrane system, can be easily removed from the protoplast by the vesicular secretion pathway and sequestered in the CW (e.g., Malone et al 1974;Woźny et al 1982;Ksią _ zek et al 1984;Hubner et al 1985;Krzesłowska and Woźny 1996;Wierzbicka et al 2007;Meyers et al 2009). Results of recent studies, concerning the uptake and sequestration of Al in A. thaliana (Illéš et al 2006) and Pb in F. hygrometrica (Krzesłowska et al 2010) have provided more compelling evidence for this phenomenon.…”
Section: Detection Of Tms In Plant Cell Wallmentioning
confidence: 99%
See 2 more Smart Citations